Penerapan Model Pembelajaran Kooperatif Tipe Quick On The Draw Untuk Meningkatkan Aktivitas Dan Hasil Belajar PKn pada materi hubungan gambar pada lambang negara dengan sila-sila pancasila kelas II MIN 8 Aceh Barat Daya - Suwirda, Erma (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The Application of the Cooperative Learning Model Type Quick On The Draw to Increase Civics Ac-tivity and Learning Outcomes in the Material Relationship Pictures on the National Symbols with the Principles of Pancasila Class II MIN 8 Southwest Aceh Aceh 2019/2020 Academic Year". The problem in this study is the low learning outcomes of Civics Education. The purpose of this class action research is to find out (1) Improvement of student learning outcomes after the implementation of the Quick On The Draw cooperative learning model (2) Student activities in learning the Quick On The Draw coopera-tive learning model. This study uses a class action research (Action Reseach) of two cycles. Each cycle consists of four stages: design, activity and observation, reflection. This research was conducted from September to November 2019. The subjects of this study were 35 students in Class II. The research ap-proach was carried out using the descriptive approach method. Data collection techniques are done using tests, observation is observation of student activities. Data processing and analysis is used by using per-centage techniques. Based on calculations and data analysis in this study shows that student learning outcomes have increased namely from the first cycle which initially only 74.29% increased 85.71% cy-cle II. The results of the analysis of student activity have increased in both cycles, from the good enough category to the good category increased to very good, so it can be concluded that by applying the Quick On The Draw type of cooperative learning models can improve the learning outcomes of class II stu-dents, as well as the learning model this can be used as an alternative to Civics learning.